Optimal and Near Optimal Price and Advertising Strategies for Finite and Infinite Horizons - Welam, Ulf Peter (Management Science, 1982)
The simplest price and advertising optimization model consistent with current empirical research is formulated and analyzed. An explicit horizon function is introduced to compare and synthesize the finite and infinite horizon situations. The practically prevalent procedure of setting this period's advertising expenditure proportional to the previous period's sales is, for good reasons, declared near optimal.